Mapeamento de QTL em cana-de-açúcar (Saccharum spp.) utilizando marcadores DArt (diversity arrays technology) e microssatélites - Nunes, Camila de Marillac Costa (2013)
The first efforts in sugarcane breeding involved crosses between polyploid species, Saccharum spontaneum L. and Saccharum officinarum L.. These crosses produced interspecific hybrids that were successively backcrossed to S. officinarum. This strategy resulted in a considerable increase in the sugarcane genome complexity. Current varieties exhibit high levels of ploidy and heterozygosity, besides varying levels of aneuploidy. These properties make the understanding of sugarcane genome more difficult; and therefore present a challenge to the development of genetic studies with this culture. Among the different approaches to perform the genetic characterization of a species, the development of genetic maps is useful in providing information about its genomic structure. In this work, we report the first linkage maps for sugarcane using both DArT (Diversity Arrays Technology) and SSR (Single Sequence Repeat) markers. We identified markers significantly associated to characters involved in sugar production. Maps were obtained using two populations: one, consisting of 81 genotypes, was derived from the selfing of a single RB97327 plant; the other, consisting of 91 genotypes, was derived from the crossing RB97327 x RB72454. Genomic DNA was extracted from axillary buds. Genotypes for twenty pairs of SSR primers and 7680 DArT markers were identified. Using mendelian segregation analysis a total of 392 DArT and 57 SSR polymorphic markers, in the population of selfing, and 632 DArT and 79 SSR polymorphic markers, in the outcrossing population, were detected to be segregating as single-dose markers. Both maps were obtained using the OneMap software. Critical values for LOD-score of 3.5 and recombination fraction of 0.3 were chosen. In the map obtained with the selfing population, 449 polymorphic markers with 3:1 segregation were used to originate 95 linkage groups for the variety RB97327. This map had a total length of 1217.2 cM. The estimated size of the genome of RB97327 was 10540.9 cM, which suggests that the obtained coverage (11.5%) is still low. For the population derived from crossing, the 711 polymorphic markers with 3:1 and 1:1 segregation originated 136 linkage groups. The map showed a total length of 2722.2 cM. The SSR markers allowed the identification of six possible homeology groups for the female parent RB97327, and nine homeology groups for the integrated map. For each population, framework maps were produced which were then used to investigate putative associations between markers and characters involved in sugar production. QTL were found both using single marker analysis and composite interval mapping. In the population derived from selfing, using single marker analysis, 63 markers were significantly associated to six variables: number of internodes, number of stems per plant, stem length, stem diameter, stem weight and percentage of soluble solids (°Brix). Using composite interval mapping, three QTL related to stem diameter, length of stem and °Brix were identified. In the population derived from the cross RB97327 x RB724554, using single marker analysis, 60 markers were significantly associated with the same six variables. Using composite interval mapping, two QTL related to diameter and length of stem were detected.